Stanowiska Kościoła katolickiego wobec liberalizmu po Soborze Watykańskim II - Dworzecka, Joanna (Humaniora. Czasopismo Internetowe, 2022)
The text is an attempt to answer the question of the direction in which the Catholic social thought of the Church is heading. Its purpose is to present the attitude of successive popes to liberalism, with particular emphasis on post-conciliar teaching against the background of historical changes. Mainly papal encyclicals and exhortations as well as conciliar documents constitutions are analysed. The article shows the continuity of the social teaching of the Church and the changes introduced by successive popes, thanks to which it is possible to grasp the direction of this teaching. The main conclusion is the acceptance by the Church of liberalism, but only in a form that takes into account human dignity, the superiority of work over capital, freedom of religion and the value of Christian morality that can constitute the foundation for the liberal order.